Development and Characterization of Biocompatible Fullerene [C60]/Amphiphilic Block Copolymer Nanocomposite - Alok Chaurasia; Nanda Gopal Sahoo; James T. McLeskey; Xiao Hu (Journal of Spectroscopy)
We report a supramolecular process for the synthesis of well-defined fullerene (C60)/polymer colloid nanocomposites in an aqueous solution via complex formation. A biocompatible triblock poly(4-vinylpyridine)-b-polyethylene-b-poly(4-vinylpyridine), P4VP8-b-PEO105-b-P4VP8, was synthesized by atom transfer radical polymerization. The block copolymer formed complexes with C60 in toluene and resulted in fullerene assembly in cluster form. Nanocomposite dispersion in an aqueous solution could be obtained using an aged solution of the polymer/C60/toluene solution by a solvent evaporation technique. The UV-Vis and FTIR spectroscopy confirmed the complex formation of fullerene with the polymer which plays a significant role in controlling the PDI and size of polymer/C60 micelles in the toluene solution. The particle size and morphology of P4VP8-b-PEO105-b-P4VP8 and P4VP8-b-PEO105-b-P4VP8/C60 mixture were studied by dynamic light scattering (DLS) and transmission electron microscopy (TEM). In a cytotoxicity test, both pure polymer and the resulting polymer/C60 composite in water showed more than 90% cell viability at 1 mg/mL concentration.